NEW MINERALOGIC DATA ON THE MAKSYUTOVO ECLOGITE-GLAUCOPHANE SCHIST COMPLEX, SOUTHERN URALS - Dobretsov N.L.; Dobretsova L.V. (My University, 1988)
The Maksyutovo complex, southern Urals, extends meridionally along the Sakmara River for over 200 km along the boundary between the Russian plate and the Magnitogorsk zone. It is one of the oldest complexes in which there is evidence that rocks were metamorphosed at pressure close to the maximum level for the Earth's crust, i.e., more than 14 kb. The authors collected and further studied samples of the same rocks on the left bank of the Sakmara River, below the village of Karayanovo. Here, on upper reaches of a left tributary creek of the Sakmara, several outcrops and debris of boudinaged quartz-jadeite rock bodies among graphite and mica schists were studied. Study results are presented. The new data, more than 100 microprobe analyses of most specific minerals, should allow the genesis of this complex to be determined more accurately and compared with that of other high-pressure metamorphic complexes.